2004
DOI: 10.1007/s00438-004-1071-z
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana expresses multiple Golgi-localised nucleotide-sugar transporters related to GONST1

Abstract: Transport of nucleotide-sugars across the Golgi membrane is required for the lumenal synthesis of a variety of essential cell surface components, and is mediated by nucleotide sugar transporters (NSTs) which are members of the large drug/metabolite superfamily of transporters. Despite the importance of these proteins in plants, so far only two have been described, GONST1 and AtUTr1 from Arabidopsis thaliana. In this work, our aim was to identify further Golgi nucleotide-sugar transporters from Arabidopsis. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
91
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 61 publications
4
91
0
Order By: Relevance
“…In Arabidopsis thaliana, the genes encoding for NSTs are similar to those encoding for plastidic triose phosphate translocators (TPTs); together, 44 NSTs and 7 TPTs form a gene family of 51 members (Knappe et al, 2003;Rautengarten et al, 2014). To date, a number of these NSTs from Arabidopsis have been functionally characterized, specifically transporters for GDP-mannose (GDP-Man), GDP-fucose (GDP-Fuc), UDP-galactose (UDP-Gal), UDP-glucose (UDP-Glc), UDP-rhamnose (UDP-Rha), and UDP-xylose (UDP-Xyl) (Bakker et al, 2005;Baldwin et al, 2001;Ebert et al, 2015;Handford et al, 2012Handford et al, , 2004Norambuena et al, 2002Norambuena et al, , 2005Rautengarten et al, 2014Rautengarten et al, , 2016Rollwitz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana, the genes encoding for NSTs are similar to those encoding for plastidic triose phosphate translocators (TPTs); together, 44 NSTs and 7 TPTs form a gene family of 51 members (Knappe et al, 2003;Rautengarten et al, 2014). To date, a number of these NSTs from Arabidopsis have been functionally characterized, specifically transporters for GDP-mannose (GDP-Man), GDP-fucose (GDP-Fuc), UDP-galactose (UDP-Gal), UDP-glucose (UDP-Glc), UDP-rhamnose (UDP-Rha), and UDP-xylose (UDP-Xyl) (Bakker et al, 2005;Baldwin et al, 2001;Ebert et al, 2015;Handford et al, 2012Handford et al, , 2004Norambuena et al, 2002Norambuena et al, , 2005Rautengarten et al, 2014Rautengarten et al, , 2016Rollwitz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, the first three proteins of these groups have been functionally characterized. One protein of the NST-KT family and one of the NST-KVAG family were shown to be UDP-Gal transporters [17] while a second protein of the NST-KVAG family might transport GDP-Man but also other nucleotide sugars [18]. These results and further extensive analysis of NST proteins revealed that the degree of sequence identity is not indicative for the substrate specificity of the transporters [6], i.e.…”
Section: Introductionmentioning
confidence: 90%
“…In Arabidopsis, 43 distinct genes encoding NSTs and seven genes (including one pseudogene) encoding pPTs could be identified while 43 NST genes and ten pPT genes were detected in rice. Only nine of the 43 NST proteins in Arabidopsis have been analyzed in detail so far, namely members of the GONST family, GONST1 to GONST4, that transport GDPMan [9,18] and two members of a family that was named UTR according to the AtUTr proteins which have been described by Norambuena and colleagues [23,24]. AtUTr1 was the first NST from plants shown to transport UDP-activated sugars, namely UDP-Gal and UDP-Glc [23] while a second transporter, AtUTr2, was shown to solely transport UDPGal [24].…”
Section: Molecular Characterization Of Atnst-kt1mentioning
confidence: 99%
See 1 more Smart Citation
“…SLC35D2 is phylogenetically related to UDP-Glc/UDP-Gal NST UTR7 17 from clade II, which also includes characterized and putative GDP-mannose transporters. 18,19 It remains to be tested whether any of the Arabidopsis NSTs from these 2 Blast similarity searches of available plant genomes revealed usually a single ROCK1 ortholog in other plant species ( Table 1) Table 1). No clear orthologous sequences were detected in available red algae genomes.…”
mentioning
confidence: 99%